2011
DOI: 10.1080/09674845.2011.11730326
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance-associated biomarkers PGP, GST-π, Topo-II and LRP as prognostic factors in primary ovarian carcinoma

Abstract: This study aims to investigate the expression of P-glycoprotein (PGP), glutathione S-transferase pi (GST-pi), DNA topoisomerase II (Topo-II) and lung resistance-related protein (LRP) in ovarian carcinoma, thus providing better chemotherapy choice and post-operative prognosis for ovarian carcinoma patients. A total of 80 primary ovarian carcinoma, 16 benign ovarian epithelial neoplasm, and 12 normal ovarian tissue samples were collected. Immunohistochemistry was used to detect the expression of PGP, GST-pi, Top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 11 publications
(9 reference statements)
1
29
0
Order By: Relevance
“…P-gp is the best-known and principal mediator of MDR. P-gp, which is encoded by MDR1, is involved in pumping chemotherapy drugs from the inside to the outside of tumor cells, and in preventing intracellular accumulation of these drugs (20,24). MRP1 functions similarly to MDR1 in reducing tumor sensitivity to chemotherapy, and it can recognize and pump out chemotherapy drugs bound to glutathione in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp is the best-known and principal mediator of MDR. P-gp, which is encoded by MDR1, is involved in pumping chemotherapy drugs from the inside to the outside of tumor cells, and in preventing intracellular accumulation of these drugs (20,24). MRP1 functions similarly to MDR1 in reducing tumor sensitivity to chemotherapy, and it can recognize and pump out chemotherapy drugs bound to glutathione in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although a great number of studies evaluated the effect of ABCB1 on EOC patients, the association between ABCB1 and EOC prognosis was still under debate. While certain amount of studies reported that high ABCB1 could predict unfavorable prognosis [23,28,30,31,34,35], quite a few did not find any significant association between ABCB1 and survival in patients with EOC [18,27,32]. The possible reasons for these inconsistent results might include (i) heterogeneities of the basic characteristics of the studies such as sample sizes, EOC subtypes, clinical stage, and populations, (ii) different intervention such as residual disease after surgery, time point of ABCB1 measurement and (iii) different methodology such as detection methods and procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] It had been confirmed that MRP and GST-π overexpression, and decreased expression of ToPo II were important mechanisms-mediated multidrug resistance. [9] So, we carried out the study of multidrug resistance (MDR) gene related proteins in post-operative individualized treatment of gastric cancer.…”
Section: Original Articlementioning
confidence: 89%